O escudo de Aquiles e a tensão entre guerra e mousiké no canto XVIII da Ilíada - Werner, Christian (2022)
The purpose of this paper is to discuss how the tension between the destruction of war and the experience provided by musical activities or, mythopoetically, to the sphere of the Muses (mousiké), permeates Iliad 18, culminating in the narration of the forging of Achilles' new shield by Hephaestus. The main passages discussed are the meeting of the Nereids as a khóros that participates in Thetis' lament for Achilles the way Achilles conceptualizes his former set of weapons and some of the aspects highlighted in the actual meeting of Thetis and Hephaestus. As for the Shield, in addition to tracking the tension between destruction and mousiké that pervades it, it is shown how this tension helps to clarify two sets of problematic verses, 535-38 and 604-5.
O objetivo deste artigo é discutir como a tensão entre a destruição própria da guerra e a experiência propiciada por atividades musicais ou, mitopoeticamente, da esfera das Musas (mousiké) perpassa o canto XVIII da Ilíada, culminando na narração da forja do novo escudo de Aquiles por Hefesto. As principais passagens discutidas são a reunião das Nereidas como um khóros que participa do lamento de Tétis por Aquiles, a forma como Aquiles conceitualiza seu antigo conjunto de armas e alguns dos aspectos ressaltados no encontro propriamente dito de Tétis e Hefesto. Quanto ao Escudo, além de rastrear-se a tensão entre destruição e mousiké que o perpassa, mostra-se como essa ajuda a esclarecer dois conjuntos de versos problemáticos, 535-38 e 604-5.
Keywords: Homer; Iliad; Achilles' shield; War; Mousiké; Homero^lpt; Ilíada; Escudo de Aquiles; Guerra; Mousiké